Liofilização de extrato fenólico do coproduto do processamento do pedúnculo do caju. - Lima, Antonia Carlota de Souza (2019)
Cashew (Anacardium occidentalle L.) is a tropical fruit whose peduncle has high content of bioactive compounds associated with health benefits. However, the main way of using it is by the juice and pulp industry, generating large quantities of co-product, which is mainly used to make animal feed. Because it possesses phenolic compounds in its composition, the Cashew Peduncle Coproduct (CPC) is a promising material for the industry, considering these compounds that are extremely sensitive to oxidizing environments. In this way, it is necessary to use technologies to preserve them, allowing their application. The objective of the study was to obtain and characterize the physical, chemical and physicochemical parameters of the CPC phenolic extracts and to evaluate the use of the lyophilization process in the preservation of the antioxidant capacity through in vitro bioaccessibility analysis. The phenolic compounds were extracted by hydroalcoholic solution and ultrasonic bath from dry CPC. After obtaining the extract, the extract compounds were identified by UPLC-QTOF-MS Ultra Performance Liquid Chromatography. The extract was lyophilized using Maltodextrin (MD), Gum arabic (GA) and its blend (MD) as carrier agents. The extracts before and after lyophilization were evaluated for retention of phenolic compounds (CF) and their antioxidant activity (ABTS and FRAP). In the lyophilizates the physical characterization (solubility, hygroscopicity, water activity (Aw) and humidity), morphology (SEM) and crystallinity (XRD) were made. Finally, the bioaccessibility of the CF and AA contents was made in the non-lyophilized and lyophilized extracts. The results showed that the extraction process contributed to the increase of CF content (ranging from 243.32 ± 14.2 in dry stalk to 376.25 ± 12.3 mg GAE / 100 g in dry extract) and AA (12.01 ± 1.5 in the dry peduncle for 70.35 ± 2.01 μM Trolox / g in the dry basis extract). Non-lyophilized extract, quercetin, gallic acid and mirecetin, as well as its glycosides and derivatives, which may have contributed to the high AA, were also identified, as well as the presence of important phytochemicals for health in SPC. The use of the carrier agents allowed protection of the CF present in the extract, although a significant decrease of these compounds in lyophilized extracts was observed (ranging from 376.25 ± 12.3 mg GAE / 100 g dry base in the non-lyophilized extract to 227.45 ± 4.7 mg GAE / 100 g dry matter for MD). However, the amount of CF in the lyophilized samples did not differ, verifying that the two types of carrier agents used resulted in the same retention of these polyphenols. The results of AA showed that the highest values (178,03 ± 2,5 and 168,12 ± 3,7 μM Fe2SO4 / g of dry matter for MD and MG, respectively) by the FRAP method were of the samples with maltodextrin in the formulation. The powders presented high solubility (> 60%), low humidity (<8%), low Aw and hygroscopicity (<4%), desirable characteristics for dry products. As for the morphology, sawdust or broken glass was observed for lyophilized extracts, characteristic of the lyophilization process, besides a predominantly amorphous structure. The bioactivity of phenolic compounds (around 30%) and AA (below 10%) after digestion resulted in a protective effect of carrier agents, since a high reduction of these compounds was observed in the non-lyophilized extract . Therefore, the use of carrier agents associated with lyophilization for the protection of CPC phenolic extract makes it possible to suggest the use of these compounds by the nutraceutical or food industry and can be used as an additive in the food in order to prolong the useful life of products, such as because it has high antioxidant activity